PERSEPSI PETANI DALAM PENERAPAN GOOD AGRICULTURE PRACTICES (GAP) KOMODITI BENGKUANG (Pachyrhizus erosus) DI KECAMATAN BINJAI SELATAN - Pakpahan, Tience Elizabet (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
Farmers perception in Applicating Good Agriculture Practices (GAP) for yam commodity (Pachyrhizus erosus) in South Binjai, Binjai City. The purpose of this study are : (1) Identify the level of farmers perception in applicating Good Agricultural Practices  (GAP) for yam commodity, (2) Identify factors that influence farmers perception (education, experience, income, information access, the role of extension worker, participation in extension, technical cultivation) in applicating Good Agricultural Practices (GAP) for yam commodity. This study was held in Binjai on 26 March until 04 Mei 2018. Methods of data collection are surveyed using the questionnaire as data collecting tool and SPSS for Windows 18 program as analyst data processing for identifying factors that influence farmers perception in applicating GAP for yam commodity. The results of study shows that level of farmers perception is high categorized (87,09%). The results of multiple linear regression is Y = 7,071 + 1,040ð‘‹1+1,666ð‘‹2 - 0,174 ð‘‹3 - 0,121 ð‘‹4+ 0,624 ð‘‹5+ 0, 087ð‘‹6 +0,402ð‘‹7, education, experience, and technical cultivation significanty effected farmers participation in applicating Good Agriculture Practices (GAP) for yam commodity, while income, informtion access, the role of extension worker and participation in extension did not significantly effected farmers participation in applicating Good Agriculture Practices (GAP) for yam commodity.